Coupling of tribovoltaic and thermoelectric effect in metal-semiconductor tip contact - Li, Jinzhao (Nanyang Technological University, 2023)
In this thesis, the research progress on the triboelectric effect and generators are reviewed. The tribovoltaic current generation mechanism between the copper needle and silicon wafer electrode is studied further through several groups of experiments. Strong synergistic enhancement of current generation by tribovoltaic voltaic and thermoelectric processes based on metal-semiconductor sliding structures are discussed